Dog Walking and Physical Activity in the United States - Sandra A. Ham, MS; Jacqueline Epping, MEd (Centers for Disease Control and Prevention, 2006)
Introduction Dog walking is a purposeful physical activity that may have health benefits for humans and canines. A descriptive epidemiology of the contribution of dog walking to physically active lifestyles among dog walkers in the United States has not been previously reported. Methods Data on youth and adults who reported walking for pet care trips (N = 1282) on the National Household Travel Survey 2001 were analyzed for number of trips, proportion walking a dog for at least 10 minutes on one trip, and accumulation of 30 minutes or more in 1 day of walks lasting at least 10 minutes. Results In 1 day, 58.9% of dog walkers took two or more walks, 80.2% took at least one walk of 10 minutes or more, and 42.3% accumulated 30 minutes or more from walks lasting at least 10 minutes each. There were no significant differences by sex, family income, or categories of urbanization. Conclusion Walking a dog may contribute to a physically active lifestyle and should be promoted as a strategy that fits within the framework set forth by the Task Force on Community Preventive Services for Physical Activity.